PENGARUH TRANSPARANSI, AKUNTABILITAS DAN PARTISIPASI MASYARAKAT TERHADAP KUALITAS LAPORAN KEUANGAN DESA DI KECAMATAN GONDANG KABUPATEN NGANJUK - Novia Rosy Pratiwi; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2022)
This paper analyzes the effect of transparency, accountability, and community participation on the quality of village financial reports in the Gondang sub-district, Nganjuk district. The case study in this study is the village apparatus in charge of managing village and community financial reports included in the village consultative body. The number of samples that can be used in this study is 120 respondents. The results of this study using the multiple linear regression analysis methods simultaneously show that the variables of transparency, accountability and public participation significantly affect the quality of financial reports. While partially 1) the transparency variable partially has a significant and positive effect on the quality of financial reports, 2) the accountability variable partially has a significant and positive effect on the quality of financial reports, 3) the community participation variable partially has a significant and positive effect on the quality of financial reportsKeywords: transparency, accountability, society participation, financial statements.